Incorporation of graphene oxide/titanium dioxide with diferent polymer materials and its efects on methylene blue dye rejection and antifouling ability - Mohamat, Rosmanisah; Abu Bakar, Suriani; Mohamed, Azmi; Muqoyyanah Muqoyyanah, Muqoyyanah Muqoyyanah; Othman, Mohd Hafz Dzarfan; Mamat, Mohamad Hafz; Malek, Mohd Firdaus; Ahmad, Mohd Khairul; Yulkifi Yulkifi, Yulkifi Yulkifi; Seeram Ramakrishna, Seeram Ramakrishna (Springer, 2023)
Exposure of synthetic dye, such as methylene blue (MB), in water bodies led to a serious threat to living things because they are toxic and non-degradable. Amongst the introduced dye removal methods, membrane separation process can be considered a powerful technique for treating dye contamination. However, this method commonly sufered from drawbacks, such as short membrane lifetime, low permeability and selectivity. To overcome these issues, graphene oxide (GO) and titanium dioxide (TiO2) were used as additives to fabricate polyethersulfone (PES)- and polyvinylidene fuoride (PVDF)-based hybrid membranes via non-solvent-induced phase separation method. Prior to membrane fabrication, GO was synthesised via electrochemical exfoliation method assisted by customised triple-tail surfactant. The potential of PES- and PVDF-based hybrid membranes for wastewater treatment has been discussed widely. However, direct comparison between these two polymeric membranes is not critically discussed for MB dye separation application yet. Therefore, this study is aimed at evaluating the performance of diferent types of polymers (e.g. PES and PVDF) in terms of membrane morphology, properties, dye rejection and antifouling ability. Results showed that the incorporation of GO and TiO2 alters the morphology of the fabricated membranes and afects dye rejection further, as well as their antifouling performance. In contrast with pristine membrane, PES-GO/TiO2 and PVDF-GO/TiO2 possessed high hydrophilicity, as indicated by their low contact angle (67.38° and 62.12°, respectively). Based on this study, PVDF-GO/TiO2 showed higher porosity value (94.88%), permeability (87.32 L/ m2 hMPa) and MB rejection rate (92.63%), as well as fux recovery ratio value of>100% as compared with others. Overall, the incorporation of GO and TiO2 with PVDF polymer are proven to be efective hybrid materials of membrane fabrication for dye rejection application in the near future. The polymer material’s intrinsic properties can afect the attributes of the fabricated membrane.